Potensi Pemberian Bakteri Penghasil IAA (Pseudomonas sp. IAA1 dan Bacillus sp. IAA2) terhadap Perkecambahan Zea mays saccharata Sturt.: Potential of Giving IAA Producing Bacteria (Pseudomonas sp. IAA1 and Bacillus sp. IAA2) on Germination of Zea mays saccharata Sturt. - Andini Widyaningsih; Siti Khotimah; Rahmawati (Universitas Negeri Semarang, 2025)
Indigenous peatland bacteria producing indole acetic acid (IAA) hormone function to help in the physiological process of plants during vegetative growth of plants. This study aims to determine the effect of giving IAA-producing bacteria (Pseudomonas sp. IAA1 and Bacillus sp. IAA2) and to determine the best density of IAA-producing bacteria for sweet corn germination (Zea mays saccharata Sturt). This study used a completely randomized design (CRD), with 8 treatment levels and 3 replications. The research data were analyzed using Ms. Excel by finding the average germination time. The results showed that the provision of IAA-producing bacteria had an effect on the germination time of sweet corn plants. The treatment of giving Bacillus sp. IAA2 bacteria with a bacterial density of 1.04 × 107 cells/mL gave the best results in the germination time of sweet corn with an average germination time of 2.00 days, while Pseudomonas sp. IAA1 has a bacterial density of 1.51 × 107 cells/mL and an average sweet corn germination time of 2.25 days. The bacterial consortium of Pseudomonas sp. IAA 1 and Bacillus sp. IAA2 has a bacterial cell density of 2.04 cells/mL and an average sweet corn germination time of 2.30 days. These indigenous bacteria producing IAA can be developed into biofertilizers so that they can replace chemical fertilizers that can harm the environment, especially the soil.